Singing at the winepress : Ecclesiastes and the ethics of work - Atkinson, Taylor (Bloomsbury T & T Clark, 2015)
Atkinson uses Qoheleth's work ethic to provide an analysis of Ecclesiastes, utilising the writings of St Bonaventure and Martin Luther. Reading Ecclesiastes within a penitential framework, Bonaventure offers a version of the contemptus mundi tradition that is rooted in his metaphysics. His commentary is ethically significant for the way he detects the vice of curiousity precipitating a perceptual rupture wherein vanity comes to signify sin and guilt. Luther, on the other hand, interprets Solomon as a wise economic-political administrator who preaches the good news of God's involvement in quoti.